Correction to: Establishing a common metric for patient-reported outcomes in cancer patients: linking patient reported outcomes measurement information system (PROMIS), numerical rating scale, and patient-reported outcomes version of the common terminology criteria for adverse events (PRO-CTCAE) - Minji K. Lee; Benjamin D. Schalet; David Cella; Kathleen J. Yost; Amylou C. Dueck; Paul J. Novotny; Jeff A. Sloan (SpringerOpen, 2021)
An amendment to this paper has been published and can be accessed via the original article.